Revisiting the Role of Master Regulators in Tomato Ripening. (March 2020) - Wang, Rufang; Angenent, Gerco C.; Seymour, Graham; de Maagd, Ruud A.
Abstract : The study of transcriptional regulation of tomato ripening has been led by spontaneous mutations in transcription factor (TF) genes that completely inhibit normal ripening, suggesting that they are 'master regulators'. Studies using CRISPR/Cas9 mutagenesis to produce knockouts of the underlying genes indicate a different picture, suggesting that the regulation is more robust than previously thought. This requires us to revisit our model of the regulation of ripening and replace it with one involving a network of partially redundant components. At the same time, the fast rise of CRISPR/Cas mutagenesis, resulting in unexpectedly weak phenotypes, compared with knockdown technology, suggests that compensatory mechanisms may obscure protein functions. This emphasises the need for assessment of these mechanisms in plants and for the careful design of mutagenesis experiments. Highlights: A string of recent publications has put into question the function of TFs, which were previously considered master regulators in the control of tomato fruit ripening. RNA interference and CRISPR/Cas9 mutagenesis have enabled a re-evaluation of their proposed functions, which were previously thought to be mostly derived from the phenotype of spontaneous ripening mutations. Three spontaneous mutations in TF genes all appear to be gain-of-function mutations and, interestingly, probably represent three different mechanisms of this phenomenon. These observations raise interesting fundamental and practical questions related to the manipulation of fruit ripening and other processes. Although CRISPR/Cas9 mutagenesis has dramatically improved our options for addressing gene function, recent results suggest that compensatory mechanisms in CRISPR mutants also hide true gene functions.